The Impact of Diet and Lifestyle on the Course of Autoimmune Diseases - Karolina Łucja Sobek; Michał Mazur; Dorota Waz; Jakub Szarłowicz; Zofia Goliszek; Wiktoria Tabin-Barczak; Aldona Sokołowska; Klaudia Fikas; Kamil Chwaliszewski; Sebastian Samuła (Quality in Sport)
Introduction and Purpose: Autoimmune diseases represent a diverse group of disorders caused by immune dysregulation, resulting in attacks on the body’s own tissues. These conditions are increasingly common and significantly impact patients' quality of life. Environmental factors, including diet and lifestyle, are key contributors to this increase. This review explores the impact of diet and lifestyle on the progression and management of autoimmune diseases.